Interaksi Mahasiswa KKN UINSU Kelompok 38 terhadap Masyarakat dalam Mengembangkan Pendidikan Karakter Qur’ani di Desa Paku Kecamatan Galang - Tri Indah Kesuma Wati; Erika Rahma Siregar (MODELING: Jurnal Program Studi PGMI, 2023)
The socialization relationship between KKN 38 uinsu students and residents in strengthening the relationship between KKN 38 students and the residents of the village of Paku, sub-district of Galang and in order to advance the quality of Qur'anic character education in the New Normal Period, because in the pandemic era yesterday the teaching and learning system experienced problems in the distribution of knowledge . So with the existence of a socialization relationship, KKN 38 students want to increase the quality of Qur'anic character learning through activities that involve the community and children in increasing the quality of Qur'anic character learning in Paku Village, Galang District.